The Effect of Repeated Reading for Developing Reading Fluency and Reading Comprehension in EFL Students: Pre Experimental Study - Amelia Husni; Dyah Sunggingwati; Ventje Jany Kalukar (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2024)
Reading is one of the skill that must be mastered by students from elementary school to college level. Reading is also one of the skill learned in learning English, especially students who study English as a foreign language. Students have difficulty reading fluently because English and Indonesian writing are different. This also has an impact on students' understanding or interpreting text in English. This study aimed to examine the effect of repeated reading on the development of reading fluency and reading comprehension. This study used a pre-experimental design method. Data collection was conducted through pretest and posttest. Data analysis was conducted used descriptive data analysis and paired sample t-tests. Based on the results of the study, it was found that repeated reading was able to improve students' reading fluency and reading comprehension, as seen from the average pretest score of 68.17 and then increased to the posttest score of 78.56. This increase increased by 8.35 points. This shows that repeated reading could improving reading fluency and reading comprehension in eighth grade students of SMP Negeri 1 Loa Janan. The implications of this research are expected to help teachers in choosing reading strategies for students learning English as a foreign language.